Omics-driven exploration and mining of key functional genes for the improvement of food and fiber crops - Naqvi, Rubab Zahra; Mahmood, Muhammad Arslan; Mansoor, Shahid; Amin, Imran; Asif, Muhammad (Frontiers in Plant Science, 2024)
The deployment of plant omics technologies has got an incredible boost over the past few decades with the advances in next-generation sequencing (NGS) technologies, innovative bioinformatics tools, and the deluge of available biological information. The major omics technologies in the limelight are genomics, transcriptomics, proteomics, metabolomics, and phenomics. These biotechnological advances have modernized crop breeding and opened new horizons to develop crop varieties with improved traits. The genomes of several crop species are sequencedsequenced, and a huge number of genes associated with different crucial economic traits have been identified. These identified genes not only provide insights into the understanding of regulatory mechanisms of crop traits but also decipher practical grounds to assist in the molecular breeding of crops. This review discusses the potential of omics technologies for the acquisition of biological information andfor the mining of the genes associated with important agronomic traits in important food and fiber crops, such as wheat, rice, maize, potato, tomato, cassava, and cotton. Different functional genomics approaches for the validation of these important genes are also highlighted. Furthermore, a list of genes, discovered by employing omics approaches are being represented as potential targets for genetic modifications by latest genome engineering methods for the development of climate-resilient crops that would in turn provide great impetus to secure global food security.